Fossil care and fossil studies: Andy Currant, former curator of the fossil mammals collections at the Natural History Museum, London. (28th January 2015) - Stringer, Chris; Delbarre, Gabrielle; Hooker, Jerry; Kruszynski, Robert; Donovan, Stephen K.; Stringer, Christopher B.
<x xml:space="preserve">Abstract</x> For over 40 years Andy Currant curated the Fossil Mammal Collections at the Natural History Museum, London, during which time he provided gentle fossil care to over 100 000 internationally important specimens collected from around the world. Specializing in the study of Pleistocene mammal bones, he rapidly became a leading research scientist in the British Quaternary faunal record. His research and fieldwork, on numerous excavations in the UK and abroad, led him to create a biostratigraphic model framework for the Quaternary mammal fauna which contributed to further knowledge about climatic changes during the later Pleistocene. As a curator, his own excavations into the Museum's collections resulted in the discovery or rediscovery of iconic historically important specimens. Copyright © 2015 John Wiley & Sons, Ltd.